Exposure to aflatoxin B1 in Thailand by consumption of brown and color rice - Panrapee I. (2017)
© 2015, Society for Mycotoxin Research and Springer-Verlag Berlin Heidelberg. This study assessed the aflatoxin B 1 (AFB 1 ) intake of the Thai population through consumption of contaminated brown and color rice. A total of 240 rice samples from two harvesting periods were collected in June/July 2012 (period I) and in December 2012/January 2013 (period II) and analyzed for AFB 1 by HPLC with fluorescence detection (limit of detection (LOD) = 0.093 ng/g). Exposure assessment was based on AFB 1 levels in rice and food intake data for rice according to Thai National Consumption. Frequency and levels of AFB 1 were higher in period I (59 %, < LOD = 26.61 μg kg −1 ) than in period II (10 %, < LOD = 3.51 μg kg −1 ). Only one sample exceeded the Thai standard limit for total aflatoxin of 20 μg kg −1 , but 12 out of 240 rice samples exceeded the European Union maximum level for AFB 1 of 2 μg kg −1 . The data showed that the quality and safety of Thai rice largely comply with the requirement for both exports and domestic consumption. According to the Thai National Consumption data, the estimated AFB 1 intake via rice consumption in period I and period II was 0.80 and 0.12 μg kg −1  bw day −1 , respectively. The potential risk for cancer, based on the recommendation of the JECFA, was estimated to be 0.011 person/year/100,000 people at a mean consumption. Although the risk via consumption of Thai rice seems to be low, the maximum levels of AFB 1 in this staple food suggest that careful monitoring and surveillance of AFB 1 contamination in rice is essential to ensure the safety of rice.